The Power of the Little Blue Pill: Innovations and Implications of Life Style Drugs in an Aging Population - Jacob LaRiviere; Hendrik Wolff (Institute for the Study of Labor (IZA), 2014)
The launch of Viagra in April 1998 led to a historically unprecedented high usage of erectile dysfunction (ED) drugs. We test whether Viagra's introduction significantly influenced outcomes for its target population such as STD rates of older men, as well as its non-target populations, such as divorces, natality, the distribution of the age spread within couples, female STDs and sexual assault rates. We find causal evidence that Viagra's introduction increased Gonorrhea rates in older men by 15-28%. We find no significant evidence of any effects on other variables. We take this as evidence that this lifestyle drug causes significant changes in choices only which affect short term outcomes, while long term planned decisions are unaffected. Overall, we find that the welfare impacts of Viagra with respect to our outcomes of interest are positive and large.
Keywords: I1; J1; O33; J31; 330; prescription drugs; STD; aging population; Viagra; differences-in-differences